Analisis Proses Perencanaan Pembelajaran Pendidikan Kesetaraan Paket B Berbasis Kurikulum 2013 di Sanggar Kegiatan Belajar (SKB) Kota Samarinda - Titra Weni (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2020)
Equivalent education package B based on the 2013 curriculum is a non-school education program that is equivalent to formal junior high school education. The delivery of education is carried out by following the curriculum that should be the 2013 curriculum and is expected to answer solutions for people who drop out of school or who need education. This study aims to find out how Equivalent Education Learning Package B based on 2013 Curriculum and what factors influence the learning process. This research was conducted at the Samarinda City Learning Activity Center specifically the Package B program. Data collection in this study using interview, observation, and documentation techniques. The results of the study showed that the implementation of equality education package B based on the 2013 curriculum in Samarinda City SKB consisted of three stages, namely planning, implementation, and assessment of learning and factors influencing the learning outcomes of citizens learning package B. by developing learning tools that will be used for learning, that is, compiling lesson plans and syllabi that are adapted to the equality education module package B curriculum 2013 and recruiting citizens to learn by open and individual socialization.